The state of development of components of speech readiness of older preschool children with speech disorders - Bielova, Olena (Special Education, 2021)
The aim of the study is to investigate the formation of the components of speech readiness for school in preschool children with speech disorders. The study used research methods that allowed to experimentally investigate the development of the components of speech readiness: cognitive, motivational and emotional. It has been established that in children with speech disorders all components of speech readiness are impaired and require specific training.